Adherence of surgeons to the World Health Organization recommendations of hand scrubbing in a tertiary care hospital in Peshawar - Riaz, Misbah; Khan, Wasim; Hussain, Fazal; Shah, Danish (International Journal of Research in Medical Sciences, 2022)
Background: In an effort to combat the global rise of wound infection, the World Health Organization (WHO) has recommended hand scrubbing guidelines for surgeons. Our study aimed to determine the adherence of surgeons in Peshawar to these recommendations. Methods: The method and duration of scrubbing for the first surgical procedure of the day was anonymously observed for 182 surgical consultants and residents in the operating theatre of Khyber Teaching Hospital Peshawar from July to August 2019 followed by a questionnaire which assessed the knowledge of the participants regarding scrubbing protocols. Data was analysed using SPSS 23. Students t test was used and p>0.05 was taken as statistically significant. Results: Out of 182 participants, 41 (22.5%) were consultants and 141 (77.5%) were residents. A total of 3 (1.6%) participants were observed to strictly adhere to the WHO standards of scrubbing. Average time taken by each surgeon was 0.95±0.6 seconds. Students t-test showed no significant difference between the mean time of consultants and residents (p>0.05). The results of the questionnaire revealed that 90.7% of the staff was aware of the WHO recommendations of scrubbing and 82.6% had noticed relevant display charts in the OT. Majority of participants (69.8%) reported that patient load and limited time were the main cause of lack of compliance. Conclusions: A serious lack of compliance to protocol was noted in the operating theatre of Khyber Teaching hospital. There is a dire need to improve scrubbing practices.